2017
DOI: 10.1093/sysbio/syx070
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting Evolutionary Histories of the Mitochondrial and Nuclear Genomes in New World Myotis Bats

Abstract: The rapid diversification of Myotis bats into more than 100 species is one of the most extensive mammalian radiations available for study. Efforts to understand relationships within Myotis have primarily utilized mitochondrial markers and trees inferred from nuclear markers lacked resolution. Our current understanding of relationships within Myotis is therefore biased towards a set of phylogenetic markers that may not reflect the history of the nuclear genome. To resolve this, we sequenced the full mitochondri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 81 publications
2
42
1
Order By: Relevance
“…This pattern may reflect the complex landscape forms that facilitate and limit gene flow such as high elevation mountains and low-lying river valleys. Platt et al (2018) shows complete discordance between mtDNA (single locus) and nuclear-derived (thousands of loci) species trees. These results provide cautionary examples of the risks of using any single marker to study relationships (Platt et al 2018), particularly if that single marker only records the gene flow mediated by one sex (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern may reflect the complex landscape forms that facilitate and limit gene flow such as high elevation mountains and low-lying river valleys. Platt et al (2018) shows complete discordance between mtDNA (single locus) and nuclear-derived (thousands of loci) species trees. These results provide cautionary examples of the risks of using any single marker to study relationships (Platt et al 2018), particularly if that single marker only records the gene flow mediated by one sex (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Stemming from the suggestion by Carstens and Dewey (2010) gene-flow' models of phylogeny, concluding gene flow occurred among these taxa during divergence prior to the Pleistocene. Until Platt et al (2018) and Morales et al (2017), phylogenies of Myotis were based on mtDNA (Dewey 2006) or combinations of mtDNA and nuclear sequences (Stadelmann et al 2007;Carstens and Dewey 2010), in which mtDNA may have swamped potentially conflicting signals from nuclear markers (Platt et al 2018). Platt et al's (2018) separate analyses of mitochondrial versus nuclear sequences revealed consistently conflicting gene trees between these markers, concluding that bifurcating phylogenies based on a single gene (ie.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for bats, for which many species are likely to have undergone rapid radiation, diversification, and potentially hybridization and/or incomplete lineage sorting (135)(136)(137)(138). In particular, genome-level data sets should at best be able to account for the phylogenetic noise inherent in analyses of single genes or at worst at least clearly indicate the degree of noise that they impart (139).…”
Section: Phylogeny and Population Genomicsmentioning
confidence: 99%
“…Yet, in the speciose order of Chiroptera, accounting for 20% of all mammal species (Burgin, Colella, Kahn, & Upham, 2018), cases of hybridization appear to be rare. For instance, the family Vespertilionidae contains about 500 species but only includes very few well-documented cases of interspecific hybrids (Afonso, Goydadin, Giraudoux, & Farny, 2017;Berthier, Excoffier, & Ruedi, 2006;Centeno-Cuadros et al, 2017), whereas cases of historical events of gene introgression exemplified by cytonuclear discrepancies are more common (Artyushin, Bannikova, Lebedev, & Kruskop, 2009;Baird, Hillis, Patton, & Bickham, 2008;Kuo et al, 2015;Morales & Carstens, 2018;Morales, Jackson, Dewey, O'meara, & Carstens, 2017;Platt et al, 2017;Trujillo, Patton, Schlitter, & Bickham, 2009;Vallo, Benda, Červený, & Koubek, 2013). However, it is possible that contemporary interspecific hybridization is underestimated, since most of the taxonomic studies conducted on bats usually rely only on mitochondrial genes for species-level recognition (Baker & Bradley, 2006;Clare, Lim, Engstrom, Eger, & Hebert, 2007;Francis et al, 2010).…”
mentioning
confidence: 99%